2021
DOI: 10.3390/cells10092491
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Frizzled-Related Protein 1 Promotes Odontoblastic Differentiation and Reparative Dentin Formation in Dental Pulp Cells

Abstract: Direct pulp capping is an effective treatment for preserving dental pulp against carious or traumatic pulp exposure via the formation of protective reparative dentin by odontoblast-like cells. Reparative dentin formation can be stimulated by several signaling molecules; therefore, we investigated the effects of secreted frizzled-related protein (SFRP) 1 that was reported to be strongly expressed in odontoblasts of newborn molar tooth germs on odontoblastic differentiation and reparative dentin formation. In de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…As for the molecular mechanisms underlying FABP4 suppression-induced pseudohypoxia in HOCF cells, in addition to HIF mechanisms, calcium-related signaling may be involved, as suggested by a previous study [ 33 ]. In support of this idea, IPA analysis indicated that (1) cell signaling was included in the top five molecular and cellular functions, (2) the calcium-binding protein S100-related signaling pathway was included in the top five canonical pathways and (3) upstream regulators NKX2-1 [ 34 ], HOXA10 [ 35 ], GATA2 [ 36 ] and CEBPA [ 37 ] and causal network master regulators NKX2-1 [ 34 ], TRPM2 [ 38 ] and SFRP1 [ 39 ] are known to regulate Ca 2+ signaling and/or mitochondrial functions.…”
Section: Discussionmentioning
confidence: 99%
“…As for the molecular mechanisms underlying FABP4 suppression-induced pseudohypoxia in HOCF cells, in addition to HIF mechanisms, calcium-related signaling may be involved, as suggested by a previous study [ 33 ]. In support of this idea, IPA analysis indicated that (1) cell signaling was included in the top five molecular and cellular functions, (2) the calcium-binding protein S100-related signaling pathway was included in the top five canonical pathways and (3) upstream regulators NKX2-1 [ 34 ], HOXA10 [ 35 ], GATA2 [ 36 ] and CEBPA [ 37 ] and causal network master regulators NKX2-1 [ 34 ], TRPM2 [ 38 ] and SFRP1 [ 39 ] are known to regulate Ca 2+ signaling and/or mitochondrial functions.…”
Section: Discussionmentioning
confidence: 99%
“…Nano β-TCP/collagen scaffolds were used in this study. Our previous studies have reported that the nano β-TCP/collagen scaffolds containing with various proteins in direct pulp capping model promote reparative dentin formation 36,37 . The concentration of proteins added to the scaffolds in vivo was higher than that of proteins stimulating cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of SFRP1 in human milk was previously reported (Molinari et al., 2012), but as SFRP1 was not detected in previous research about bovine milk and colostrum (Le et al., 2011; Nissen et al., 2017; Zhang et al., 2015a, 2015b), it was detected in bovine colostrum (up‐regulation on high‐quality colostrums) for the first time in this study. As SFPR‐1 is known to regulate the growth and differentiation of certain cell types and to have antiproliferative effects on vascular cells (Bodine et al., 2009; Molinari et al., 2012, Ipposhi et al, 2021) it is thought that it may be similar to TETN, which plays a role in supporting high mitotic activity in newborns.…”
Section: Discussionmentioning
confidence: 99%